Conservação e eliminação de DNAs satélites: a diferenciação do cromossomo W em Triportheus (Teleostei: Characiformes) - Oliveira, Mariannah Pravatti Barcellos (Universidade Federal de São Carlos, 2023)
The evolution of sex chromosomes raises several issues that have yet to be resolved, like why are repeated sequences often species-specific on sex chromosomes prone to accumulating? To better explore this, this work aims to trace the dynamics of satellite DNAs (satDNAs) accumulation and elimination along the pathway of W chromosome differentiation using the well-known Triportheus fish model. This fish genus stands out due to a conserved ZZ/ZW sex chromosome system present in all examined species. While the Z chromosome is conserved in all species, the W chromosome is smaller and exhibits differences in size and morphology. The presumed ancestral W chromosome is comparable to that of Triportheus auritus and contains 19 different SatDNA families accumulating on it. The results found in the analysis of five additional Triportheus species showed that most of these repetitions were probably eliminated as speciation was taking place and the W chromosomes continued their path of differentiation, while the Z chromosomes of some species began to accumulate some TauSatDNAs. Additional species-specific SatDNAs that made up the heterochromatic region of each of these chromosomes were most likely amplified after that. Therefore, the W chromosomes of the various Triportheus species have undergone significant evolutionary changes in a short period of time (15–25 Myr) after their divergence.
Conservation and elimination of satellite DNAs: the differentiation of the W chromosome in Triportheus (Teleostei: Characiformes)
Keywords: Citogenômica; Cromossomos sexuais; DNA repetitivo; Cytogenomics; Sex Chromosomes; Repetitive DNA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL